Identifying major pesticides affecting bivalve species exposed to agricultural pollution using multi-biomarker and multivariate methods - Damasio, Joana
The aim of this investigation was to identify major pesticides that may cause detrimental effects in bivalve species affected by agricultural pollution. Investigations were carried out using freshwater clams (Corbicula fluminea) transplanted in the main drainage channels that collect the effluents coming from agriculture fields in the Ebro Delta (NE Spain) during the main growing season of rice (from May to August). Environmental hazards were assessed by measuring simultaneous up 46 contaminant levels and 9 biomarker responses. Measured biological responses showed marked differences across sites and months. Antioxidant and esterase enzyme responses were in most cases inhibited. Lipid peroxidation levels increased steadily from May in upstream stations to August in drainage channels. Principal Component (PCA) and Partial Least Squares to Latent Structure regression (PLS) analyses allowed the identification of endosulfan, propanil, and phenylureas as being the chemical contaminants causing the most adverse effects in the studied species.